Bias temperature instabilities in 4H SiC metal oxide semiconductor field effect transistors: Insight provided by electrically detected magnetic resonance. (February 2018) - Lenahan, P.M.; Anders, M.A.; Waskiewicz, R.J.; Lelis, A.J.
Abstract: We present insight with regard to the physical mechanisms of negative bias temperature instabilities (NBTI) in 4H SiC based metal oxide semiconductor field effect transistors (MOSFETs) based upon electrically detected magnetic resonance measurements (EDMR). Most of this insight results from EDMR studies not directly focused upon NBTI but studies more broadly focused upon two fundamental questions. (1) What as-processed defects are present at and near the SiC/oxide interface? (2) How does the presence of oxide charge alter electrically active defects at the SiC/dielectric interface? We compare the SiC results to magnetic resonance studies of bias temperature instabilities in silicon based devices. Although our analysis admittedly provides only a partial understanding of the phenomena in SiC devices, the analysis does allow for some reasonably definitive conclusions. The NBTI phenomena in 4H SiC MOSFETs are certainly different than in Si based MOSFETs. (1) Interface dangling bonds do not appear to play a significant role in SiC MOSFET interface traps under multiple circumstances, suggesting strongly that they are not significant contributors to NBTI. (2) Although oxide defects, almost certainly including the well-known E′ family of oxide traps, play an important role in SiC device NBTI, other defects, surprisingly including defects within the SiC substrate, are also involved. Highlights: Oxygen deficient silicons in the oxide apparently play an important role in SiC MOSFET NBTI. The atomic scale mechanics of NBTI in SiC MOSFETs are significantly different from the NBTI mechanisms in Si MOSFETs. This manuscript provides insight into NBTI phenomena in 4H SiC MOSETs. The insight results from electrically detected magnetic resonance studies of these devices.